A dádiva nas organizações: presentes como vínculos comunicacionais pela presença-na-ausência e a criação de espaços conforto para a comunicação - Liberatore, Silvia T. (2010)
When people (or organizations) exchange gifts, there are more meaningful interventions in those acts than actions of offering, accepting and thanking (giving back or not) may seem to express. Concepts related to situations and purposes that are ingrained in the memory of the past and that will determine relationships in the future are created or reinforced. The present work aims at highlighting the simple habit of giving gifts, so common that it passes by unnoticed but which can help build and strengthen bonds. Among different organized social groups there is no survival without support, as there is not a person who is not a giver and a receiver of attention at the same time, either by objective means that can be evaluated directly or by abstract actions, which are less likely to be defined. All in all, there is a wide range of possibilities to find some criteria in writings from different authors in several areas (already defined) of knowledge and others begin to form. The essential reciprocity of the gift is the common element of communication and its equivalent reason for existing: without reciprocity there is no communication, there is no social group that can organize itself and therefore survive. It is in this reciprocity of attention (and of objects) that knowledge is added, new habits are created, and cultures can mingle and integrate: these are the simultaneous experiences and experimentations which establish inclusion amongst common cultural background. In the present research, the foundation for the understanding of rituals of object exchanging as social contracts is laid on the works of authors such as Mauss and Bystrina while the look on the Latin-American reality, especially the Brazilian one, is from Gruzinski, Canclini, and (Viveiros de) Castro, which show what was, is and can be the exchange of gifts as the creation of new contexts that include different cultures. Other authors are important for the course of the research and many are not mentioned here but they are crucial for the beginning and the end of the purpose of this study. Objects which are gifts (bonding celebrations) and presents (that keep their memories in the absence), indicate alterations incorporated in situations of giving presents, hypothesis of this research when analyzing the communication strategy in company cases and real life examples